Metabolic and Functional Evaluation of the Heart and Lungs in Pulmonary Hypertension by Gated 2-[18F]-Fluoro-2-deoxy-D-glucose Positron Emission Tomography. (April 2017) - Saygin, Didem; Highland, Kristin B.; Farha, Samar; Park, Margaret; Sharp, Jacqueline; Roach, Emir Charles; Tang, W.H. Wilson; Thomas, James D.; Erzurum, Serpil C.; Neumann, Donald R.; DiFilippo, Frank P.
Pulmonary hypertension (PH) is associated with a metabolic shift towards glycolysis in both the right ventricle and lung. This results in increased glucose uptake to compensate for the lower energy yield of glycolysis, which creates a potential for 2-[18F] fluoro-2-deoxy-D-glucose (FDG) positron emission tomography (PET) to be a useful tool in the evaluation of participants with PH. We investigated the utility of PET for PH by comparing FDG-PET uptake in the right ventricle and lungs in 30 participants with PH and eight healthy controls and correlating these measurements with echocardiographic (ECHO) measurements and other traditional assessments commonly used in PH. All participants underwent gated FDG-PET scanning in the fasting state, ECHO, six-minute walk test (6MWT), and blood draw for NT-proBNP. Participants also completed the CAMPHOR questionnaire. Right ventricular (RV) end-diastolic and end-systolic volumes, RV ejection fraction, and FDG uptake by PET were significantly different between PH and healthy controls and strongly correlated with plasma NT-proBNP levels and RV ECHO parameters including TAPSE, RV systolic pressure, Tei index, and global peak systolic strain. In addition, lung standardized uptake value (SUV) was also found to be significantly higher in participants with PH than healthy controls. However, lung SUV did not show any significant correlations with NT-proBNP levels, 6MWT, or functional and pressure measurements by ECHO. In this study, we demonstrated the ability to evaluate both lung and right heart metabolism and function in PH by using a single gated FDG-PET scan.